The Influence of Financial Knowledge, Financial Socialization on Financial Satisfaction with Financial Risk Attitude as a Mediation Variable in Millennial Generation in Padang City - Hanifa Asti Afriani; Rizki Sri Lasmini (Universitas Negeri Padang, 2023)
This research has a purpose to analyze the influence of financial knowledge, financial socialization on financial satisfaction with financial risk attitude as a mediating variable in the millennial generation in Padang City. The population in this research is the millennial generation who already have income in the city of Padang. The total of samples in this research were 210 respondents. Data collection through distributing questionnaires online and processed data using SmartPLS software. The results of this research point that (1) financial knowledge has a significant effect on financial risk attitude , (2) financial socialization has no significant effect on financial risk attitude , (3) financial risk attitude has a significant effect on financial satisfaction , (4) financial knowledge has a significant effect on financial satisfaction , (5) financial socialization has a significant effect on financial satisfaction , (6) financial knowledge has no significant effect on financial satisfaction with financial risk attitude as mediation, (7) financial socialization has no significant effect on financial satisfaction with financial risk attitude as mediation.